Particulate matter flux interception in oceanic mesoscale eddies by the polychaete Poeobius sp. (13th July 2018) - Christiansen, Svenja; Hoving, Henk‐Jan; Schütte, Florian; Hauss, Helena; Karstensen, Johannes; Körtzinger, Arne; Schröder, Simon‐Martin; Stemmann, Lars; Christiansen, Bernd; Picheral, Marc; Brandt, Peter; Robison, Bruce; et al.
Abstract: Gelatinous zooplankton hold key functions in the ocean and have been shown to significantly influence the transport of organic carbon to the deep sea. We discovered a gelatinous, flux‐feeding polychaete of the genus Poeobius in very high abundances in a mesoscale eddy in the tropical Atlantic Ocean, where it co‐occurred with extremely low particle concentrations. Subsequent analysis of an extensive in situ imaging dataset revealed that Poeobius sp. occurred sporadically between 5°S–20°N and 16°W–46°W in the upper 1000 m. Abundances were significantly elevated and the depth distribution compressed in anticyclonic modewater eddies (ACMEs). In two ACMEs, high Poeobius sp. abundances were associated with strongly reduced particle concentrations and fluxes in the layers directly below the polychaete. We discuss possible reasons for the elevated abundances of Poeobius sp. in ACMEs and provide estimations showing that a single zooplankton species can completely intercept the downward particle flux by feeding with their mucous nets, thereby substantially altering the biogeochemical setting within the eddy.